2016
DOI: 10.1177/0145721716662917
|View full text |Cite
|
Sign up to set email alerts
|

Depression Screening in Diabetes Care to Improve Outcomes

Abstract: Depression screening rates among individuals with diabetes and no history of MDD were remarkably low. Patients with diabetes but no MDD diagnosis who sought health care at a FQHC clinic had more depressive symptoms than those with a history of MDD at both sites. Individuals with diabetes and who have a MDD diagnosis are much more likely to receive regular depression screening than those without MDD, which leaves a substantial proportion of patients with undetected depression. Depression screening must be enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…This is consistent with prior research. 7,8 We found that people who score lower on measures of depressive symptoms (Ͻ3 on the PHQ2) have nearly 60 percent lower odds of being assessed (i.e. screened and/or treated) than people with higher PHQ scores (Ն3) scores.…”
Section: Key Findingsmentioning
confidence: 81%
See 1 more Smart Citation
“…This is consistent with prior research. 7,8 We found that people who score lower on measures of depressive symptoms (Ͻ3 on the PHQ2) have nearly 60 percent lower odds of being assessed (i.e. screened and/or treated) than people with higher PHQ scores (Ն3) scores.…”
Section: Key Findingsmentioning
confidence: 81%
“…7 A retrospective observational study of diabetic patients found that only 11% of patients with no history of depression (but who had depressive symptoms) were screened. 8 Another question is the extent to which depression screening is being implemented equitably, that is, if some populations are more likely to receive screening than others. Adherence to clinical practice guidelines can be an important tool for reducing health inequities, while unequal implementation of preventive services can exacerbate existing disparities in health outcomes.…”
mentioning
confidence: 99%
“…If a practice does not have access to mental health specialists, mental health screening tools, or a reminder system to alert providers to screen for mental health conditions on a routine basis, depression and diabetes distress may go undetected. 14,28…”
Section: Screening Recommendations For Depression and Diabetes Distressmentioning
confidence: 99%
“…24 At the practice level, adding prompts to electronic health records can promote screening for depression and diabetes distress, re-evaluations, treatment, and referrals. 14,25…”
Section: Strategies To Improve Screening For Depression and Diabetes mentioning
confidence: 99%
See 1 more Smart Citation